POTENTIAL ANTIOXIDANT ACTIVITY OF SURUHAN LEAF AND STEM EXTRACT (Peperomia pellucida L. Kunth) USING THE DPPH METHOD AND DETERMINATION OF PHENOLIC AND FLAVONOID LEVELS - Sodik, Jajang Japar; Budiana, Wempi; Roni, Asep; Wahyudin (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Antioxidants are compounds that are capable of neutralizing free radicals. One plant with potential antioxidant properties is Peperomia pellucida. Objective: This study aimed to determine the antioxidant activity, total phenolic content, and total flavonoid content of extracts of the leaves and stems of Peperomia pellucida. Methods: Antioxidant activity was tested using the DPPH method, while the total phenolic and flavonoid contents were measured using UV-Vis spectrophotometry. Extraction was performed via reflux using three different solvents: n-hexane, ethyl acetate, and ethanol. Results: The highest antioxidant activity was found in the ethanol extract of the leaves, with an IC50 value of 36.85 µg/mL, and in the stems, with an IC50 value of 71.28 µg/mL. The highest total phenolic content in the ethanol extract of the leaves was 14.46 mg GAE/g and that in the stems was 12.82 mg GAE/g. The highest total flavonoid content in the ethanol extract of the leaves was 12.12 mg QE/g and that in the stems was 10.49 mg QE/g. Conclusion: The results indicated that the ethanol extract of Peperomia pellucida leaves exhibited very strong antioxidant activity. Keywords: antioxidants, DPPH, phenolic, flavonoids, suruhan Plants